2020
DOI: 10.3390/ijerph17165658
|View full text |Cite
|
Sign up to set email alerts
|

The Burnout Syndrome in Medical Academia: Psychometric Properties of the Serbian Version of the Maslach Burnout Inventory—Educators Survey

Abstract: The aim of this study was to assess the psychometric properties of the Maslach Burnout Inventory—Educators Survey (MBI-ES). The presence of burnout syndrome, its relationship with personality traits, intention to change career and work abroad were assessed in a cross-sectional multi-center trial conducted among educators at three medical faculties in the Western Balkans during 2019. Translation and cultural adaptation were made based on internationally accepted principles. Personality traits were assessed by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 41 publications
3
4
0
1
Order By: Relevance
“…Individuals who score high on conscientiousness focus on achieving job-related goals and remain positive in the workplace ( Zellars et al, 2000 ). These findings are also consistent with the traditional view that conscientious individuals are high performers in various job contexts ( Vukmirovic et al, 2020 ). The personality trait of emotional stability is negatively related to teacher burnout, and teachers with high emotional stability experienced less burnout at work.…”
Section: Discussionsupporting
confidence: 91%
“…Individuals who score high on conscientiousness focus on achieving job-related goals and remain positive in the workplace ( Zellars et al, 2000 ). These findings are also consistent with the traditional view that conscientious individuals are high performers in various job contexts ( Vukmirovic et al, 2020 ). The personality trait of emotional stability is negatively related to teacher burnout, and teachers with high emotional stability experienced less burnout at work.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, a high subscale score on achievement means that the subject feels fulfilled professionally (the achievement subscale is inverted). In a previous study performed by our team in a similar population, analysis of internal consistency yielded a Cronbach’s alpha of 0.785, indicating scale reliability [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…the greater the sense of personal accomplishment, the lower the level of burnout [14]. The analysis for internal consistency of the Serbian version of the MBI-ES questionnaire showed that Cronbach's alpha coefficient for the emotional exhaustion subscale was 0.93, while alpha coefficients for depersonalization and personal accomplishment subscales were 0.61 and 0.77, respectively [23]. The reliability of the MBI-ES scale is very good; the Cronbach's alpha coefficients on our sample for the subscales of emotional exhaustion, depersonalization, and personal accomplishment are 0.93, 0.75, 0.79, respectively.…”
Section: Outcome Measuresmentioning
confidence: 99%